Pesticide Exposure During Development Does Not Affect the Larval Pheromones, Feeding Rates, or Morphology of Adult Honey Bee (Apis mellifera) Queens - Walsh, Elizabeth M.; Khan, Omar; Grunseich, John; Helms, Anjel M.; Ing, Nancy H.; Rangel, Juliana (Frontiers in Ecology and Evolution, 2021)
Recent work demonstrated that honey bee (Apis mellifera L.) queens reared in pesticide-laden beeswax exhibit significant changes in the composition of the chemicals produced by their mandibular glands including those that comprise queen mandibular pheromone, which is a critical signal used in mating as well as queen tending behavior. For the present study, we hypothesized that pesticide exposure during development would alter other queen-produced chemicals, including brood pheromone in immature queens, thus resulting in differential feeding of queen larvae by nurse workers, ultimately impacting adult queen morphology. We tested these hypotheses by rearing queens in beeswax containing field-relevant concentrations of 1) a combination of tau-fluvalinate and coumaphos, 2) amitraz, or 3) a combination of chlorothalonil and chlorpyrifos. These pesticides are ubiquitous in most commercial beekeeping operations in North America. We observed nurse feeding rates of queen larvae grafted into pesticide-laden beeswax, analyzed the chemical composition of larval queen pheromones and measured morphological markers in adult queens. Neither the nurse feeding rates, nor the chemical profiles of immature queen pheromones, differed significantly between queens reared in pesticide-laden wax compared to queens reared in pesticide-free wax. Moreover, pesticide exposure during development did not cause virgin or mated adult queens to exhibit differences in morphological markers (i.e., body weight, head width, or thorax width). These results were unexpected given our previous research and indicate that future work is needed to fully understand how pesticide exposure during development affects honey bee queen physiology, as well as how various adult queen quality metrics relate to each other.